Hydrophilic extract of Pistacia vera pericarp protects against phenylhydrazine-induced hepatotoxicity and hemolytic anemia - Fatemeh Amin; Najmeh Parvaz; Nahid Askari; Morteza Khademalhosseini; Sakineh Kahanamani Falahati-pour; Iman Fatemi; Fatemeh Khajehasani; Zahra Taghipour; Soudeh Khanamani Falahati-pour (Mashhad University of Medical Sciences, 2024)
Objective: Pistacia vera is commonly used in traditional medicine to treat various disorders. This study aims to investigate the anti-anemia and hepatoprotective effects of Pistacia vera pericarp extract (PVPE) in a rat model of phenylhydrazine (PHZ)-induced anemia.Materials and Methods: PVPE was prepared using the maceration method. The extract was administered at doses of 20, 80, and 160 mg/kg for 28 days to normal and PHZ-treated rats. The effects of PVPE were evaluated in terms of changes in biochemical, histological, hematological, and molecular biomarkers in the liver and blood.Results: Administration of PVPE to the anemic animals significantly restored these deleterious effects on hematological parameters compared to the anemic group. Kupffer cell activation was seen in the liver tissue of the anemic rats. Administration of PVPE mitigated these deleterious effects.Conclusion: PVPE has potent antioxidant activity and may represent a promising treatment for anemia and liver protection in clinical settings.